The Phytoestrogenic Potential of Yam Bean (Pachyrhizus erosus) on Ovarian and Uterine Tissue Structure of Premenopausal Mice - Cicilia Novi Primiani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2015)
The use of estrogen hormone by public has significantly been improved either as prevention or treatment of disease. Menopausal issues in women are often treated using hormone replacement therapy. In regard to this, yam bean is found to contain genistein and daidzein compounds with a chemical structure that resembles estrogen hormone, therefore yam bean is categorized in the phytoestrogen group. The purpose of this study was to identify the potential of yam bean on ovarian and uterine histology of mice. This research employed a Completely Randomized Design of experimental research approach of one factor namely yam bean in three different dosage treatment: 0.3 g/kg, 0.6 g/kg, and 0.9 g/kg of yam bean for 24 days. The surgery and organ harvesting of ovary and uterus were conducted on Day 25 along with the making of histological preparat using paraffin method and Hematoxylin-eosin (HE) staining. The data was then analyzed descriptively. This research found that there were both secondary and tertiary follicle proliferation as the antrum contains some estrogen level. Meanwhile, the endometrial tissue of the uterus experienced uterine glandular proliferation. To conclude, yam bean was found to be a natural estrogen source.